2020
DOI: 10.3991/ijet.v15i01.11431
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Syrian Student Refugees towards Blended Learning: Implications for Higher Education Institutions

Abstract: This study investigates the Syrian refugees ' perceptions of blended learning (BL) at Arab Open University in Jordan as well as the effects of age and gender on participants' perceptions. A questionnaire was used to collect data from 93 Syrian refugees. Results revealed that the Syrian refugees have positive perceptions of the BL approach, and they are satisfied with it as it plays a transformative role in achieving their academic goals without negatively affecting their work and family affairs. Results also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Thirdly, utilization of facilities in Learning Management Systems (LMS) for the learning process is minimal. Usage is still limited to learning material repositories, and there are not many interactive features between instructors and students (Al-Husban & Alshorman, 2020). The use of online learning systems in Indonesia has begun to move from merely utilizing LMS and other ICTbased tools.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, utilization of facilities in Learning Management Systems (LMS) for the learning process is minimal. Usage is still limited to learning material repositories, and there are not many interactive features between instructors and students (Al-Husban & Alshorman, 2020). The use of online learning systems in Indonesia has begun to move from merely utilizing LMS and other ICTbased tools.…”
Section: Introductionmentioning
confidence: 99%
“…This includes raising completion rates and helping refugee graduates find suitable employment (Crea et al, 2015, Crea 2016., Crea et al, 2017Reinhardt et al, 2018). What is promising is the growth in partnerships between local host communities, the private sector and academic institutions, which are paving the way for innovative solutions to fill this gap (Al-Husban et al, 2020). These consist of flexible or connected learning approaches that combine online and in-person teaching with mentoring and internship programs.…”
mentioning
confidence: 99%
“…The research results in the analyzed papers hardly provided any conclusive data regarding the socio-demographic variables of participating students. A recent bibliographic review of the research that included results relative to gender and age in the use of BL [91] concluded that there were no significant differences in participants' perceptions according to gender. On the other hand, age did present significant differences, as older people considered the use of BL to be more positive.…”
Section: Discussionmentioning
confidence: 99%